Factor Analysis Of Factors Causing Delays In EPC Projects Using Dmaic And Alternative Solutions - Febri Chrishardiyan; Tukhas Shilul Imaroh (Al-Makki Publisher, 2023)
The development of the construction world today, especially in EPC (Engineering, Procurement and Construction) project work is very rapid and complex. So the level of difficulty and the potential for delays is quite large. From data taken at one of the EPC divisions of construction companies in Jakarta in March 2023, there are 9 projects that experience delays from 10 existing projects. So the purpose of this study is to identify and analyze the main factors causing delays in completing EPC projects as well as alternative completion. In achieving good project time performance, it requires the support of resources (Man, Material, Machine, Money, Method) that are owned efficiently from the input process to the output. The method used in this study is DMAIC (Define, Measure, Analyze, Improve & Control) where analysis is carried out using Fishbbone, 5W + 1H Brainstorming and Pareto Diagram. The main factors causing delays in EPC project work are lack of material supply, lack of manpower, late material arrival schedule, damage or loss of materials, lack of experts and design errors during planning. Alternatives to solving EPC project delays are first submitting an EOT (Extention of Time), adding man power, evaluating schedules, monitoring the implementation of engineering designs, and collaborating with consultants who are more experienced in the EPC field so that there are no planning design errors and implementation methods.